399 BEHAVIORAL AND ENVIRONMENTAL FACTORS IN DETERMINING PHYSICAL ACTIVITY AND OBESITY IN CHILDREN WITH CONGENITAL HEART DISEASE. (1st January 2006) - Doshi, N.; Chang, R. K.; Rodriguez, S.; Lee, M.
Abstract : Purpose: There is an increasing prevalence of obesity and dramatic decline in physical activity among American youth, including children with congenital heart disease (CHD). Little is known regarding the causes of decreased physical activity, impact on health, and relationship of decreased physical activity and obesity to other cardiovascular risk factors. We sought to evaluate behavioral and environmental variables as determining factors for physical activity and obesity in children with CHD. Methods: Healthy children and children with CHD, aged 6-13 years old, were recruited. Children with CHD were further subdivided into CHD I (after repair without significant residual limitations) and CHD II (after palliative procedure with residual limitations). Parents completed the Child Behavior Checklist, Child Vulnerability Scale, and Parent Protection Scale. Children completed a Physical Activity Determinants Questionnaire. Chi-square tests and linear regression were used for data analysis. Results: There were no significant differences between the healthy subjects and those with CHD in Child Behavior Checklist subcategories of withdrawal, anxiety/depression, thought problems, delinquency, somatic problems, social problems, attention problems, and aggression. There was no difference in parent overprotection between healthy patients and those with CHD I and CHD II using the Parent Protection Scale. CHD II children were perceived as more vulnerable by parents than healthy subjects on the Childhood Vulnerability Scale ( p = .02). Perceived child vulnerability correlates well with parent overprotection among subjects with CHD ( p = .01) but not in the healthy group. Child vulnerability also correlates with body mass index (BMI) in healthy subjects ( p = .05) but not in CHD groups. Self-efficacy for physical activity has significant correlation with BMI in all study subjects ( p = .05). Conclusion: Parents of children with CHD consider their children more vulnerable and perceived vulnerability is associated with parent overprotection. Higher child vulnerability is also associated with higher BMIs. Parental overprotection may lead to physical activity restriction in some children. Therefore, perception of child vulnerability and parental overprotection in children with CHD may represent a risk factor for physical inactivity and, ultimately, towards development of obesity.